2023
DOI: 10.2147/ijwh.s417186
|View full text |Cite
|
Sign up to set email alerts
|

Rare Occurrence of Left Ampullary Ectopic Pregnancy After Ligation of the Left Fallopian Tube: A Case Report

Abstract: Purpose Ectopic pregnancy (EP) is rare among patients having received tubal ligation; in these cases, a fertilized ovum is implanted in the proximal tube stump. Distal tubal EP cases in patients having undergone ipsilateral tubal ligation and who have relatively intact contralateral adnexa are extremely rare. Here, we report a case of pregnancy in the distal stump of the ipsilateral fallopian tube following fallopian tubal isthmus ligation. Case Presentation A 28-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 12 Subsequently, Lin CM and Xue Ke documented a rare instance of a left ampullary ectopic pregnancy subsequent to the ligation of the left fallopian tube. 3 , 8 Both of these ectopic pregnancies occurred after resection of the ipsilateral proximal fallopian tube. In this case, distinct from the cases described in the literature above, the patient had previously undergone a left adnexectomy due to torsion of the pedicle of a left ovarian cyst, left part of the proximal fallopian tube tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 Subsequently, Lin CM and Xue Ke documented a rare instance of a left ampullary ectopic pregnancy subsequent to the ligation of the left fallopian tube. 3 , 8 Both of these ectopic pregnancies occurred after resection of the ipsilateral proximal fallopian tube. In this case, distinct from the cases described in the literature above, the patient had previously undergone a left adnexectomy due to torsion of the pedicle of a left ovarian cyst, left part of the proximal fallopian tube tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 Some tubal stump pregnancies occur secondary to post-tubal ligation. 3 , 8 We report a case of spontaneous tubal stump pregnancy after partial salpingectomy due to torsion of the left ovarian cyst pedicle.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[6][7][8] Ke et al reported an ampullary ectopic that followed a tubal ligation. 9 Three consecutive tubal pregnancies following partial salpingectomies have been documented. 10,11 Contralateral fertilization of ovum with migration across the peritoneum, tubal recanalization and transperitoneal migration of ovum or spermatozoon have been documented as possible explanations of pregnancies.…”
Section: Discussionmentioning
confidence: 99%